A Tight Correlation between Millimeter and X-Ray Emission in Accreting Massive Black Holes from <100 mas Resolution ALMA Observations - Claudio Ricci; Chin-Shin Chang; Taiki Kawamuro; George C. Privon; Richard Mushotzky; Benny Trakhtenbrot; Ari Laor; Michael J. Koss; Krista L. Smith; Kriti K. Gupta; Georgios Dimopoulos; Susanne Aalto; et al. (The Astrophysical Journal Letters, 2023)
Recent studies have proposed that the nuclear millimeter continuum emission observed in nearby active galactic nuclei (AGNs) could be created by the same population of electrons that gives rise to the X-ray emission that is ubiquitously observed in accreting black holes. We present the results of a dedicated high-spatial-resolution (∼60–100 mas) Atacama Large Millimeter/submillimeter Array (ALMA) campaign on a volume-limited (<50 Mpc) sample of 26 hard X-ray (>10 keV) selected radio-quiet AGNs. We find an extremely high detection rate (25/26 or ${94}_{-6}^{+3} % $ ), which shows that nuclear emission at millimeter wavelengths is nearly ubiquitous in accreting SMBHs. Our high-resolution observations show a tight correlation between the nuclear (1–23 pc) 100 GHz and the intrinsic X-ray emission (1 σ scatter of 0.22 dex). The ratio between the 100 GHz continuum and the X-ray emission does not show any correlation with column density, black hole mass, Eddington ratio, or star formation rate, which suggests that the 100 GHz emission can be used as a proxy of SMBH accretion over a very broad range of these parameters. The strong correlation between 100 GHz and X-ray emission in radio-quiet AGNs could be used to estimate the column density based on the ratio between the observed 2–10 keV ( ${F}_{2--10\,keV}^{obs}$ ) and 100 GHz ( F _100 GHz ) fluxes. Specifically, a ratio $log(F_{2--10\,keV}^{obs}/F_{100\,GHz})\leqslant 3.5$ strongly suggests that a source is heavily obscured ( $log(N_{{\rm{H}}}/{cm}^{-2})\gtrsim 23.8$ ). Our work shows the potential of ALMA continuum observations to detect heavily obscured AGNs (up to an optical depth of one at 100 GHz, i.e., N _H ≃ 10 ^27 cm ^−2 ), and to identify binary SMBHs with separations <100 pc, which cannot be probed by current X-ray facilities.